Champlain Judged by His Indian Policy: A Different View of Early Canadian History - Trigger, Bruce G. (Anthropologica, 2022)
Samuel de Champlain has commonly been pictured by historians as a man who understood Indians and was generous and considerate in his dealings with them. This paper, based on a re-study of Champlain's own writings, reveals that he understood little about the Indians with whom he had dealings and that he was uninterested in learning more about them. Rebuffs brought about by his unfamiliarity with Indian ways, and growing anxiety about his own career led to an increasingly hostile and manipulative attitude towards them. These attitudes caused him to favour a policy of assimilation for groups he felt were dependent on the French and of genocide against groups like the Iroquois, whom he perceived as being inveterately hostile.